2015
DOI: 10.1186/s13069-015-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Wntless in myeloid cells exacerbates liver fibrosis and the ductular reaction in chronic liver injury

Abstract: BackgroundMacrophages play critical roles in liver regeneration, fibrosis development and resolution. They are among the first responders to liver injury and are implicated in orchestrating the fibrogenic response via multiple mechanisms. Macrophages are also intimately associated with the activated hepatic progenitor cell (HPC) niche or ductular reaction that develops in parallel with fibrosis. Among the many macrophage-derived mediators implicated in liver disease progression, a key role for macrophage-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 73 publications
3
41
0
Order By: Relevance
“…In contrast to the increase in MMP7, advanced fibrosis was associated with reduced serum MMP1, which may suggest a perturbation in the balance between matrix deposition and degradation contributes to progressive fibrosis. In support of this, MMP1 levels were previously reported to be elevated in patients with mild fibrosis compared to healthy controls, but diminished in cirrhosis[26], and we recently demonstrated exacerbated fibrosis in mice deficient in macrophage Wnt production which was associated with reduced Mmp13 expression (the murine ortholog of MMP1)[28]. AFP, a hepatoblast marker, is used clinically as a biomarker for HCC, although an association with fibrosis has previously been observed in chronic HBV[29], and reduced AFP levels were associated with fibrosis regression following interferon therapy in patients with chronic HCV[30].…”
Section: Discussionsupporting
confidence: 53%
“…In contrast to the increase in MMP7, advanced fibrosis was associated with reduced serum MMP1, which may suggest a perturbation in the balance between matrix deposition and degradation contributes to progressive fibrosis. In support of this, MMP1 levels were previously reported to be elevated in patients with mild fibrosis compared to healthy controls, but diminished in cirrhosis[26], and we recently demonstrated exacerbated fibrosis in mice deficient in macrophage Wnt production which was associated with reduced Mmp13 expression (the murine ortholog of MMP1)[28]. AFP, a hepatoblast marker, is used clinically as a biomarker for HCC, although an association with fibrosis has previously been observed in chronic HBV[29], and reduced AFP levels were associated with fibrosis regression following interferon therapy in patients with chronic HCV[30].…”
Section: Discussionsupporting
confidence: 53%
“…One previous report showed TLR4-and TRIF-dependent induction of Wisp1 expression and WISP1-driven inflammation in a liver ischemiareperfusion injury model. 43 As we and others have implicated WNT proteins in the liver injury response, 15,53,54 it will be informative to assess whether the effect of TRIF-deficiency on WISP1-driven liver inflammation is a consequence of impaired TRIF-mediated WNT ligand expression.…”
Section: Wnt10amentioning
confidence: 99%
“…[11][12][13][14] Studies in patients and animal models suggest WNT proteins shape inflammation and tissue repair. 11,12,[15][16][17][18][19][20] The current paradigm suggests WNT ligands exert pro-inflammatory or immune-modulatory functions, depending on whether they activate b-catenin-independent or b-catenin-dependent signaling. This model largely relies on studies using the prototypical WNT ligands WNT5A and WNT3A as triggers for b-catenin-independent and b-catenin-dependent signaling, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Two previous reports (32,42) have demonstrated differing effects of myeloid Wnts in mouse models of cholestatic damage. Our data, deleting Wnt5a from myeloid cells, appears to support the conclusions drawn by Okabe et al, who showed that loss of myeloid Wnt production through the loss of Wls resulted in a reduced fibrotic response in DDC model of biliary injury.…”
Section: Inhibition Of Wnt Ligand Production Results In Reduced Biliamentioning
confidence: 92%
“…Previous studies have shown that loss of Wnt ligand export in myeloid (using LysM--Cre) (32,42) or epithelial (using Albumin--Cre)(32) cells through Wls deletion, can alter the number of regenerating ductules or levels of fibrosis in biliary disease. However it remains unclear whether this effect is due to altered canonical or non--canonical Wnt signalling.…”
Section: Inhibition Of Wnt Ligand Production Results In Reduced Biliamentioning
confidence: 99%